Quality of life and menopausal symptoms in women with liver transplants Qualidade de vida e sintomas da menopausa em mulheres transplantadas hepáticas - Luiz Francisco Baccaro; Ilka de Fátima Boin; Lúcia Costa-Paiva; Aarão Mendes Pinto-Neto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2013)
PURPOSE: To assess quality of life and climacteric symptoms in women with and without liver transplants. METHODS: This was a cross-sectional study of 52 women undergoing follow-up at a university hospital in southeastern Brazil from February 4th, 2009 to January 5th, 2011. Twenty-four of these women were 35 years old or older and had undergone liver transplantation at least one year before study entry. The remaining 28 women had no liver disease and were matched by age and menstrual patterns to the patients with transplants. The abbreviated version of the World Health Organization (WHOQOL-BREF) questionnaire was used to assess quality of life. Menopausal symptoms were assessed using the Menopause Rating Scale (MRS). Statistical analysis was carried out by Student's t-test, Mann-Whitney test and analysis of variance. Correlations between MRS and the WHOQOL-BREF were established by correlation coefficients. RESULTS: The mean age of the women included in the study was 52.2 (±10.4) years and the mean time since transplantation was 6.1 (±3.3) years. Women with liver transplants had better quality of life scores in the environment domain (p=0.01). No difference was noted between the two groups in any domain of the MRS. For women in the comparison group, there was a strongly negative correlation between somatic symptoms in the MRS and the physical domain of the WHOQOL-BREF (p<0.01; r=-0.8). In contrast, there was only a moderate association for women with liver transplants (p<0.01; r=-0.5). CONCLUSIONS: Women with liver transplants had better quality of life scores in the domain related to environment and did not exhibit more intense climacteric symptoms than did those with no liver disease. Climacteric symptoms negatively influenced quality of life in liver transplant recipients, although less intensely than in women without a history of liver disease. OBJETIVO: Avaliar a qualidade de vida e os sintomas do climatério em mulheres com e sem transplante de fígado. MÉTODOS: Estudo de corte transversal com 52 mulheres em acompanhamento ambulatorial em um hospital universitário na região sudeste do Brasil no período de 04/02/09 a 05/01/11. Dessas mulheres, 24 tinham 35 anos ou mais e haviam sido submetidas a transplante de fígado a pelo menos um ano antes do início do estudo. As outras 28 mulheres não tinham doença hepática e suas idades e padrões menstruais eram similares ao das transplantadas hepáticas. Para avaliação da qualidade de vida foi usada a versão abreviada do questionário da Organização Mundial da Saúde (WHOQOL-bref). Os sintomas da menopausa foram avaliados através do Menopause Rating Scale (MRS). A análise estatística foi realizada através dos testes t de Student, Mann-Whitney e ANOVA. As correlações entre o MRS e o WHOQOL-bref foram realizadas através de coeficientes de correlação. RESULTADOS: A idade média das mulheres incluídas no estudo foi de 52,2 (±10,4) anos e o tempo médio desde a realização do transplante foi de 6,1 (±3,3) anos. As mulheres transplantadas hepáticas tiveram melhores escores de qualidade de vida no domínio relacionado ao meio ambiente (p=0,01). Não houve diferença entre os dois grupos em nenhum domínio do MRS. As mulheres no grupo de comparação tiveram uma correlação fortemente negativa entre os sintomas somáticos do MRS e o domínio físico do WHOQOL-bref (p<0,01; r=-0,8), diferentemente das mulheres com transplante de fígado que tiveram uma correlação apenas moderada (p<0,01; r=-0,5). CONCLUSÕES: As mulheres com transplante de fígado tiveram melhores escores de qualidade de vida no domínio relacionado ao meio ambiente e não tiveram sintomas climatéricos mais intensos. Os sintomas do climatério influenciaram negativamente a qualidade de vida nas transplantadas hepáticas, porém com menor intensidade do que nas mulheres sem antecedentes de doença hepática.